1978
DOI: 10.1128/iai.20.2.552-558.1978
|View full text |Cite
|
Sign up to set email alerts
|

Purification of cholera toxin and its subunits: new methods of preparation and the use of hypertoxinogenic mutants

Abstract: Cholera toxin was obtained in pure form by fractionation on two phosphocellulose columns successively. Cholera toxin and choleragenoid were quantitatively and selectively adsorbed to the first column in 10 mM phosphate buffer, pH 7.0, and were subsequently eluted with buffer of high ionic strength. The toxin was then separated from choleragenoid on the second column by chromatography at pH 8.3. The toxin obtained was highly active and pure as judged by electrophoresis, isoelectric focusing, and various immunol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
37
1
2

Year Published

1979
1979
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 19 publications
4
37
1
2
Order By: Relevance
“…This behavior was consistent with the apparent coordinate control of A and B subunit synthesis previously observed for various hypotoxinogenic mutants (6,22). These observations suggested that hypertoxinogenic mutations, as well as all tox mutations (6,10,16,22) thus far described, belong to the broad class of "regulatory" mutations which alter the levels of toxin produced rather than the toxin molecule per se.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…This behavior was consistent with the apparent coordinate control of A and B subunit synthesis previously observed for various hypotoxinogenic mutants (6,22). These observations suggested that hypertoxinogenic mutations, as well as all tox mutations (6,10,16,22) thus far described, belong to the broad class of "regulatory" mutations which alter the levels of toxin produced rather than the toxin molecule per se.…”
supporting
confidence: 87%
“…Mutants altered in the production of toxin (tox mutants) have been isolated in several laboratories, but most of these appear to be regulatory mutants that produce greatly reduced levels of toxin (6,10,16,22). A tox regulatory site that mediates the hypoproduction of cholera toxin was reported by Vasil and co-workers (3,23) to be weakly linked to the his-1 locus of V. cholerae.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The following were purchased: Male Sprague Dawley rats from ARS/Sprague Dawley and Holtzman Co., Madison, WI, U.S.A.; chromatographically purified collagenase from Millipore, Freehold, NJ, U.S.A.; a-Chymotrypsin from Worthington Biochemical Corp., Freehold, NJ, U.S.A.; hyaluronidase, bovine plasma albumin (fraction V), soybean trypsin inhibitor, L-glutamine, fl-nicotinamide adenine dinucleotide (DPN), cholera toxin (vibrio cholera, lyophilized powder prepared and purified according to Mekalanos, Collier & Romig (1978)…”
Section: Methodsmentioning
confidence: 99%
“…Nach Zentrifugation 30 min bei 10000 X g wurde der Uberstand fur weitere Untersuchungen verwendet (KUNREL u. ROBERTSOX 1979 b). -Hexametaphosphat : 0,25 g pro 100 ml Extrakt, dann Zutropfen von verdiinnter Essigsiiure bi8 pH 4,7 (MEKALANOS et al 1978).…”
unclassified